Dynamic fingerprinting of sub-cellular nanostructures by image mean square displacement analysis. Issue 1 (December 2017) - Digiacomo, Luca; D'Autilia, Francesca; Durso, William; Tentori, Paolo; Caracciolo, Giulio; Cardarelli, Francesco
Abstract Here we provide demonstration that image mean square displacement (i MSD) analysis is a fast and robust platform to address living matter dynamic organization at the level of sub-cellular nanostructures (e.g. endocytic vesicles, early/late endosomes, lysosomes), with no a-priori knowledge of the system, and no need to extract single trajectories. From eachi MSD, a unique triplet of average parameters (namely: diffusivity, anomalous coefficient, size) are extracted and represented in a 3D parametric space, where clustering of single-cell points readily defines the structure "dynamic fingerprint ", at the whole-cell-population level. We demonstrate that different sub-cellular structures segregate into separate regions of the parametric space. The potency of this approach is further proved through application to two exemplary, still controversial, cases:i ) the intracellular trafficking of lysosomes, comprising both free diffusion and directed motion along cytoskeletal components, andii ) the evolving dynamic properties of macropinosomes, passing from early to late stages of intracellular trafficking. We strongly believe this strategy may represent a flexible, multiplexed platform to address the dynamic properties of living matter at the sub-cellular level, both in the physiological and pathological state.